Pecorino romano : les transformations d’un produit d’origine protégée au cours des xixe et xxe siècles - Rita d’Errico (Les Cahiers de Framespa)
Although its name refers to the Roman countryside, the region of Lazio from which it comes, Pecorino romano –the most exported Italian cheese until the late 20th century– is currently produced mainly in Sardinia, while that produced in Lazio is increasingly marginal and risks disappearing from the market. This evolution is partly due to factors internal to the local context, such as the profound transformation of the productive and environmental structure of the Pecorino region of origin, following the recovery of the Roman countryside during the mid-20th-century decades. This is also partly due to external factors, such as competition with other regions, where pecorino production was cheaper and less dependent on local customs. This article sets out to present the main stages of the process that saw a deep change in the link between the Pecorino romano and its territory of origin during the 19th and 20th centuries.